Nettle (Urtica cannabina L.) polysaccharides as a novel dietary supplement: enhancing systemic antioxidant status via modulation of the gut–liver axis - Zhang, Jize; Zhang, Qian; Zhang, Xiaoqing; Qiao, Jiang; Wang, Jingwei; Gao, Yang; Dong, Ping (Frontiers in Pharmacology, 2025)
BackgroundNettle (Urtica cannabina L.) is a promising traditional food source with great potential in the expanding functional foods market; however, the bioactive potential of its polysaccharides, a major component, remains underexplored as a functional food ingredient. This study evaluated the effects of U. cannabina polysaccharides (UP) on gut microbiota modulation and systemic antioxidant activity in healthy mice.MethodsMice were fed a basal diet or diets supplemented with low (300 mg/kg) (UPL) and high (600 mg/kg) (UPH) doses of UP for 28 days.ResultsOur findings revealed that UP supplementation, particularly at low doses, significantly improved growth performance (P < 0.05), serum lipid profiles (P < 0.05), and hepatic and serum antioxidant capacity without inducing liver damage. Notably, UPL treatment reduced malondialdehyde (MDA) levels (P < 0.01) and enhanced the activities of superoxide dismutase (SOD), glutathione peroxidase (GSH-PX), catalase (CAT), and total antioxidant capacity (T-AOC) (P < 0.05). Sequencing of 16S rRNA indicated that UP supplementation altered gut microbiota composition, particularly by increasing the relative abundance of beneficial genera such as Parabacteroides (P = 0.0973) and Dubosiella (P = 0.0648) in the UPL group, which were positively correlated with antioxidant biomarkers. Moreover, UPL treatment elevated levels of short-chain fatty acids (SCFAs), especially acetate and butyrate (P < 0.05). Untargeted metabolomics demonstrated that UPL treatment influenced serum metabolic profiles and enriched the bile acid (BA) secretion pathway, with notable increases in deoxycholic and taurocholic acid, suggesting a potential link between gut microbiota, BA metabolism, and host antioxidant status.ConclusionThese findings indicate that UP could serve as a safe and effective functional dietary supplement capable of improving antioxidant function through gut microbiota modulation and gut–liver axis signaling.